Biomarkers of Chronic Renal Tubulointerstitial Injury. (September 2019) - Bagnasco, Serena M.; Rosenberg, Avi Z.
Progression of renal parenchyma injury is characterized by increasing interstitial fibrosis and tubular atrophy, irrespective of the cause. Histopathologic assessment of renal tissue obtained by biopsy remains the gold standard for determining the presence and extent of tubulointerstitial scarring. Discovery of robust non-invasive means for capturing a snapshot and for longitudinal monitoring of parenchymal deterioration has been the focus of intense multimodal effort by investigators within the renal community and beyond. Research in this field has included the use of in vitro and in vivo experimental models and has fostered the development and evaluation of tissue and biofluid assays for novel analytes with potential translation to the diagnosis and prognosis of kidney disease. Here, we examine recent advances in the search of "biomarkers" for detection of renal tubulointerstitial scarring and prediction of renal outcome in human renal disease.